Creating Muhammadiyah 9 Malang Elementary School As A Children-Friendly School In Preventing Children To Be Victims Of Violence In School Environment - Erdianti, Ratri Novita; Wasis, Wasis; Fatih, Sholahudin Al (Jurnal Pengabdian Hukum Indonesia (Indonesian Journal of Legal Community Engagement) JPHI, 2021)
Child-friendly schools are a form of guaranteeing children's rights in the learning process at school. In building a child-friendly city, it is necessary to have a friendly school to make it happen. Muhammadiyah 9 Elementary School Malang City is a school that is about time to implement a child-friendly school. This service is carried out to turn Muhamadiyah 9 Elementary School into a child-friendly school by prioritizing children's interests as the main objective of learning during school. Through the process of mentoring, counseling, and consultation It is hoped that this service will be able to create a child-friendly school that is expected by all parties. With the participation of the Muhammadyah 9 Elementary School Malang, this service will be able to guarantee children's rights and in the end, one of the principles of protection in the form of the best interests of the child will be realized. . Thus the dedication will be beneficial for all parties, especially the Muhamadiyah elementary school 9 Malang city. Keywords: Child friendly schools, child protection, children's rights